The effect of socioeconomic position in the experience of disability among people with mental disorders - Antunes, Ana (2018)
AA receives a grant from the Portuguese Foundation for Science and Technology (FCT) [ grant number PD/BD/105822/2014]. The Portuguese Mental Health Study was carried out by the Department of Mental Health, NOVA Medical School, NOVA University of Lisbon, with collaboration of the CESOP-Portuguese Catholic University and was funded by the Champalimaud Foundation, the Gulbenkian Foundation, the Foundation for Science and Technology (FCT) and the Ministry of Health. The Portuguese Mental Health Study was carried out in conjunction with the World Health Organization WMH Survey Initiative which is supported by the National Institute of Mental Health (NIMH; R01MH070884), the John D. and Catherine T. MacArthur Foundation, the Pfizer Foundation, the U.S. Public Health Service (R13-MH066849, R01-MH069864 and R01 DA016558), the Fogarty International Center (FIRCA R03-TW006481), the Pan American Health Organization, Eli Lilly and Company, Ortho-McNeil Pharmaceutical, GlaxoSmithKline and Bristol-Myers Squibb.